Design implementation and characterization of JFET based color sensors - Arumugam Ashviny (Nanyang Technological University, 2021)
Optoelectronics have many industrial and commercial applications such as optical sensing, data storage, color sensing etc. This project is set to build, fabricate and analyze the optical characteristics of Junction Field Effect Transistor.